Patent Strategy and Management - Somaya, Deepak (Journal of Management, 2012)
This review reorganizes and reconceptualizes extant research on patent strategy, which has emerged from diverse roots in economics, law, and management. Accordingly, it is anticipated that this review will help provide structure and direction to what is currently a somewhat disparate and fractured field of study within management. The main proposed framework highlights two important themes within patent strategy research—generic patent strategies and the strategic management of patents. In addition, it is noted that research in each of these themes generally maps onto one or more of three key domains—rights, licensing, or enforcement—within which patent-related strategic actions are typically undertaken. Two summary tables of prior research are provided that juxtapose the three patent strategy domains with different theory lenses adopted in patent strategy research. Finally, the article highlights two promising areas whose connections with patent strategy are beginning to be addressed by research—firms’ overall appropriability strategies and value creation strategies. An overarching conceptual figure maps the different research areas reviewed in the article and highlights the relationships between these research literatures. The reconceptualization and reframing of prior research advanced in this review promises to advance scholarship on patent strategy by illuminating its many links with the broader management field and by identifying opportunities to address important unanswered research questions. It thus provides a useful roadmap to help stimulate and guide future management research in this vital area.